Cross-continental comparison of safety and protection measures amongst urologists during COVID-19 - de la Rosette, Jean J. M. C. H.; Laguna, Pilar; Alvarez Maestro, Mario; Eto, Masatoshi; Mochtar, Chaidir Arif; Albayrak, Selami; Mendoza-Valdes, Arturo; Ong, Teng Aik; Khadgi, Sanjay; Al-Terki, Abdullatif; Bolton, Damien; Gomez, Reynaldo; et al. (Wiley, 2020)
Objectives To determine the well-being of urologists worldwide during the coronavirus disease 2019 pandemic, and whether they have adequate personal protective equipment knowledge and supplies appropriate to their clinical setting. Methods Urologists worldwide completed a Societe Internationale d'Urologie online survey from 16 April 2020 until 1 May 2020. Analysis was carried out to evaluate their knowledge about protecting themselves and others in the workplace, including their confidence in their ability to remain safe at work, and any regional differences. Results There were 3488 respondents from 109 countries. Urologists who stated they were moderately comfortable that their work environment offers good protection against coronavirus disease 2019 showed a total mean satisfaction level of 5.99 (on a "0 = not at all" to "10 = very" scale). A large majority (86.33%) were confident about protecting themselves from coronavirus disease 2019 at work. However, only about one-third reported their institution provided the required personal protective equipment (35.78%), and nearly half indicated their hospital has or had limited personal protective equipment availability (48.08%). Worldwide, a large majority of respondents answered affirmatively for testing the healthcare team (83.09%). Approximately half of the respondents (52.85%) across all regions indicated that all surgical team members face an equal risk of contracting coronavirus disease 2019 (52.85%). Nearly one-third of respondents reported that they had experienced social avoidance (28.97%). Conclusions Our results show that urologists lack up-to-date knowledge of preferred protocols for personal protective equipment selection and use, social distancing, and coronavirus disease 2019 testing. These data can provide insights into functional domains from which other specialties could also benefit.
Keywords: COVID-19; Pandemic; Personal Protective Equipment; Protective Measures; Urology